Aggregation-induced polarization (AIP) of derivatives of BINOL and BINAP. Issue 46 (18th October 2022) - Tang, Yao; Yuan, Qingkai; Wang, Yu; Zhang, Sai; Wang, Jia-Yin; Jin, Shengzhou; Xu, Ting; Pan, Junyi; Guilbeau, Collin Ray; Pleasant, Alyssa Jenae; Li, Guigen
Abstract : The relationship between optical rotations of derivatives of BINOL and BINAP with water% in THF has been established resulting in optical rotation amplification and adjustment, defined as aggregation-induced polarization (AIP). Abstract : The relationship between optical rotations of small chiral molecules with water% in THF has been established. The typical aggregation co-solvent systems resulted in optical rotation amplification and adjustment, defined as aggregation-induced polarization (AIP). The AIP work can serve as a new tool to determine molecular aggregation, especially for those that cannot display aggregation-induced emission (AIE). Therefore, AIP and AIE are anticipated to complement each other. In addition, AIP can also serve as a new transmission tool providing adjusting right- or left-hand polarized lights of a series of individual wavelengths. Since chiral phosphine derivatives are among the most important ligands, this work would benefit research using chiral aggregates to control asymmetric synthesis and catalysts. Therefore, it will find many applications in chemical and materials sciences.